Preliminary Evidence for cue-induced Alcohol Craving Modulated by Serotonin Transporter Gene Polymorphism rs1042173 - Ait-Daoud, Nassima; Seneviratne, Chamindi; Smith, Justin B.; Roache, John D.; Dawes, Michael A.; Lei, Liu; Wang, Xin-Qun; Johnson, Bankole A. (Frontiers in Psychiatry, 2012)
We previously have shown that cue-induced alcohol craving and propensity for higher drinking are modulated by allelic differences in SLC6A4. In an independent study, we characterized a functional polymorphism, rs1042173 (G/T), in the SLC6A4 3′-untranslated region (3′-UTR); the T allele was associated with lower mRNA and protein levels, and the alcohol-dependent (AD) individuals carrying the TT genotype showed higher drinking intensity compared with G-allele carriers. Building upon these findings, we hypothesized that the low-expressing TT genotype associated with intense drinking would predict higher craving for alcohol in AD individuals. In this pilot study, we sought to test our hypothesis by examining 34 Hispanic AD volunteers (mean age, 34.8 years) for rs1042173 genotype-based (i.e., TT vs. TG/GG (Gx)) differences in subjective response to alcohol. We employed a human laboratory paradigm and analyzed the data using a linear mixed-effects model to assess treatment, cue procedures, and genotype main effects as well as the two-way interaction effects between them. On subjective “urge to drink” and “crave for a drink”, we found a significant main effect of the cue experiment (p ≤ 0.01) and an interaction effect between genotype and cue effects (p < 0.05). TT genotype was associated with higher intensity of drinking and craving for alcohol. Our results not only support the hypothesis that rs1042173 is a genetic marker for cue-induced alcohol craving among AD males but also are suggestive of a neurobiological mechanism associated with the rs1042173-TT genotype that triggers a disproportionate craving in response to alcohol consumption, which in turn may lead to more intense drinking. Future studies with larger sample sizes are needed to characterize the interactive effects of the serotonin transporter-linked polymorphic region (5′-HTTLPR)-L-allele reported in our previous study and of the rs1042173-TT genotype on cue-induced alcohol craving.